2021
DOI: 10.3389/fimmu.2020.577655
|View full text |Cite
|
Sign up to set email alerts
|

CD80 on Human T Cells Is Associated With FoxP3 Expression and Supports Treg Homeostasis

Abstract: CD80 and CD86 are expressed on antigen presenting cells (APCs) and their role in providing costimulation to T cells is well established. However, it has been shown that these molecules can also be expressed by T cells, but the significance of this observation remains unknown. We have investigated stimuli that control CD80 and CD86 expression on T cells and show that in APC-free conditions around 40% of activated, proliferating CD4+ T cells express either CD80, CD86 or both. Expression of CD80 and CD86 was stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“… 41 , 42 CD86 and CD80, the ligands for CTLA4, have also been shown to be expressed on CD4 + and CD8 + T cells. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 CD86 and CD80, the ligands for CTLA4, have also been shown to be expressed on CD4 + and CD8 + T cells. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…HBx interacts with IPS-1 and RIG-1 to inhibit the activation of type 1 interferon [ 39 , 42 ]. CD80 activates the T-cell costimulatory receptor CD28 [ 43 , 44 ]. HLA class I (HLA-I) glycoproteins present antigens to cognate CD8 + T cells for driving immune responses [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that there is a certain relationship and the expression of IPS-1 and PD-L1 [37][38][39], but the specific mechanism study. As it is well known, IPS-1 and RIG-1 trigger the signaling pathway o feron, which is an important part of antiviral activity in innate immunit interacts with IPS-1 and RIG-1 to inhibit the activation of type 1 interferon activates the T-cell costimulatory receptor CD28 [43,44]. HLA class I (HL teins present antigens to cognate CD8 + T cells for driving immune respons upregulation of IPS-1, RIG-1, CD80, and HLA-1 indicates that the codeliv would promote antiviral immune responses.…”
Section: Il-12 Expression and Reversal Of Immnuosuppression In Hepato...mentioning
confidence: 99%
“…iNOS является ферментом, участвующим в продукции важного провоспалительного цитотоксического агента оксида азота (NO), который защищает хозяина от различных патогенов путем инактивации и уничтожения инфекционных агентов [53]. CD80 и CD86 располагаются на поверхности антигенпрезентирующих клеток и отвечают за передачу сигналов Т-клеткам, когда они взаимодействуют со своими лигандами CD152 и CD28 [54]. FcgRI (CD64), FcgRII (CD32) и FcgRIII (CD16) являются рецепторами Fc-γ (FcgR), которые опосредуют фагоцитоз, высвобождение медиаторов воспаления и стимуляцию иммунного ответа в макрофагах [55].…”
Section: фенотипические признаки м1-и м2-макрофаговunclassified